PENERAPAN MODEL DELIKAN SEBAGAI UPAYA PENINGKATAN KUALITAS PEMBELAJARAN IPS-SEJARAH DI SMP MUHAMMADIYAH IV YOGYAKARTA - Dyah Kumalasari (ISTORIA: Jurnal Pendidikan dan Sejarah, 2008)
AbstractFor students at Junior High School, the subject of social studies is very bored tobe heared. Learning method is one of several factors that cause these problem. The goal of our research is to apply the delikan method to improve the quality of social studies learning at Junior High School.This class action research uses recommendation from Kurt Lewin models involving a spiral of cycles: initial idea, reconnaissance (fact finding), general plan, implement, and evaluate. We implements two cycles in which paper in first cycles and comic in second cycles. Delikan is a learning method involves hear (de), see (li), and done (kan). For implement this method we divide class on eight groups. For each groups, we give one theme for their task.From our research, we conclude that implementation of Delikan method lead improvement on social studies subject at Junior High School level. We have four parameters indicating the fenomenon. First, students have done the task with happy. They have a pleasant time to improve their ability to write and draw. Second, students enjoy work together in group collaboration with their classmate. This method can improve social relations between the students. Third, this method can exploit another student’s competencies, for example: write, draw etc. Finally, delikan motivate students to further learn with read another sources: book, magazine, internet, etc.Keyword: delikan, social studies, method of learning.